The use of cash flows metrics in CEO compensation and the design of loan contracts - Gong, Guojin; Jiang, Xin Daniel; Xie, Biqin (Contemporary Accounting Research, 2024)
Abstract This study examines whether using cash‐flow‐based performance metrics (CFM) in CEO compensation contracts affects the design of loan contracts. Cash‐flow‐based performance evaluation explicitly motivates the CEO to improve the firm's cash flows, which may enhance debt repayment ability and reduce credit risk. We thus hypothesize that lenders, anticipating this incentive effect, offer lower loan spreads and reduce cash‐flow‐based performance covenants when firms use CFM in CEO compensation contracts. Consistent with our expectation, the use of CFM is associated with lower loan spreads and less use of cash‐flow‐based performance covenants. These findings remain robust after we account for endogeneity. Furthermore, these results are more pronounced in firms with higher credit risk or risk of cash flow shortfalls, suggesting that lenders consider internally generated cash flows more valuable when borrowers face higher external financing costs or have greater liquidity concerns. Additionally, we find that using CFM is associated with improved cash flow performance and enhanced creditworthiness, which supports the notion that CFM is an effective incentive mechanism. Overall, our evidence suggests that lenders consider the incentive effect of cash‐flow‐based performance evaluation in the debt contracting process.